Adaptation as a Dimension of Translation - Gayathree, S. (South Eastern University of Sri Lanka, 2016)
Adaptation is known as one of the dimensions in translation. Here the content is directed towards the culture of the target readership and adjustments are made according to the target culture. In fact, when a message is transferred from the source language to the target language, the translator also deals with two different cultures at the same time. As far as adaptation is concerned, the success could be achieved by the proper transference. The Great Renunciation ‘The Light of Asia’ has been adapted into Tamil by KavimaniThesikavinayakampillai. KavimaniThesikavinayakampillai created ‘Asia Jothi’ as a spontaneous overflow in Tamil. It carries the content of Edwin Arnold’s ‘The Light of Asia’. This study aims at finding out the various forms of adaptation employed by KavimaniThesikavinayakampillai in AsiyaJothi. The first Chapter named Book the First – theBuddha’s Birth is taken for the discussion in the present study. Finding out the strategies or techniques used by KavimaniThesikavinayakampillai in substituting the ideas may be a loadstar to the budding translators. This paper identifies the techniques and strategiesemployed by KavimaniThesikavinayakampillaiand it may help the budding translators to meet the satisfaction of the target readership. Awareness in the various forms of adaptation enriches the performance of translation. In this respect adaptation is viewed as a dimensionof translation. Thus, the present study gets the significance for research. The primary sources of this study are Edwin Arnold’s ‘The light of Asia’ and KavimaniThesikavinayakampillai’s ‘Asia Jothi’.